2014
DOI: 10.1016/j.stem.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

BMP Signaling and Its pSMAD1/5 Target Genes Differentially Regulate Hair Follicle Stem Cell Lineages

Abstract: Hair follicle stem cells (HFSCs) and their transit amplifying cell (TAC) progeny sense BMPs at defined stages of the hair cycle to control their proliferation and differentiation. Here, we exploit the distinct spatial and temporal localizations of these cells to selectively ablate BMP signaling in each compartment and examine its functional role. We find that BMP signaling is required for HFSC quiescence and to promote TAC differentiation along different lineages as the hair cycle progresses. We also combine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(179 citation statements)
references
References 46 publications
9
170
0
Order By: Relevance
“…Furthermore, inhibition of BMP signals promotes Wnt signals in hair follicle stem cells, which induce hair follicle morphogenesis (Jamora et al 2003). Indepth genomic profiling of hair follicle stem cells and transient-amplifying cells revealed that GATA3, Id1 and Id3, targets of phosphoSmad1/5, play important roles in the specification of hair follicle lineages (Genander et al 2014). These findings suggest that epithelial and mesenchymal interactions mediated by BMP signals in combination with Wnt and Shh signals play important roles in the regulation of maintenance and lineage specification of hair follicle stem cells during hair cycle.…”
Section: Hair Follicle Developmentmentioning
confidence: 99%
“…Furthermore, inhibition of BMP signals promotes Wnt signals in hair follicle stem cells, which induce hair follicle morphogenesis (Jamora et al 2003). Indepth genomic profiling of hair follicle stem cells and transient-amplifying cells revealed that GATA3, Id1 and Id3, targets of phosphoSmad1/5, play important roles in the specification of hair follicle lineages (Genander et al 2014). These findings suggest that epithelial and mesenchymal interactions mediated by BMP signals in combination with Wnt and Shh signals play important roles in the regulation of maintenance and lineage specification of hair follicle stem cells during hair cycle.…”
Section: Hair Follicle Developmentmentioning
confidence: 99%
“…We identified Foxc1, a gene encoding the transcription factor Forkhead box C1 (FOXC1), as an early transcription factor expressed during developing HFs (12) and in adult Bu-HFSCs (13), and as a downstream target of BMP-pSMAD1 signaling (14). Upon conditionally ablating Foxc1 from HFs, we discovered that HFs lose the ability to maintain their old bulge in part because of a reduction in E-cadherin at SC intercellular junctions.…”
mentioning
confidence: 99%
“…Relation of this protein with AR signaling is unclear. ID1 and ID2 are key BMP signaling target transcriptional factors, and their important role was shown in mice hair follicle as well as in other organs [71]. Most probably, ID1 and ID2 overexpression marked the BMP signaling activation in DP cell samples at the time point 1 h after DHT treatment.…”
Section: Ar-related Differentially Expressed Genes In Microarray Withmentioning
confidence: 96%
“…Both BMP and WNT signaling can regulate each other. Quiescence happens due to reciprocal negative feedback loops in these signaling pathways [71,72]. In mice, Bmp2 and Bmp4 gene expression as well as expression of Dkk1 and Sfrb4 genes inhibit the expression of WNT family genes and thus limit hair follicle development to the stage of refractory telogen [70].…”
Section: Bulge Stem Cells Renewal Pathwaymentioning
confidence: 99%
See 1 more Smart Citation